Pengaruh Gender Terhadap Level Berpikir Geometri Mahasiswa - Dwi Novitasari; Nourma Pramestie Wulandari; Nilza Humaira Salsabila (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2021)
The purpose of this study was to identify the geometric thinking level of students and determine the effect of gender on the geometric thinking level of pre-service mathematics students. This study is quantitative where data analysis using Mann Witney test. The sample of this research is 55 pre-service mathematics students prospective students consisting of 33 women and 22 men. The instrument in this study is the Van Hiele Geometry Test which consists of 25 multiple-choice questions. The data were analyzed using the Mann-Whitney U test. The results showed that male students were 36.36% at the visualization level, 40.91% at the analytical level, 9.09% at the informal deduction level, 9.09% at the rigor level. and the remaining 4.55% are in the pre-recognition category. Meanwhile, for female students, as many as 27.27% at the visualization level, 33.33% at the analytical level, 18.18% at the informal deduction level, 3.03% at the deduction level, 3.03% at the rigor level, and the remaining 15 .15% are in the pre-recognition category. In addition to the categories above, based on data analysis, it was found that there was no gender effect on the students' geometric thinking level.